The effect of ability and motivation on job satisfaction and employee performance - Jasiyah, Rabiyatul (Archives of Business Research, 2018)
This study aims to analyze the influence of ability and partial motivation on job satisfaction and employee performance mediated by job satisfaction. This research was conducted at the Regional Office of Directorate General of Treasury, Ministry of Finance of Republic of Indonesia (DJPBN) Southeast Sulawesi. A sample of 220 employees and data were analyzed using confirmatory factor analyses with AMOS Ver. 22. The results of this study indicate that the ability and motivation partially have a direct effect on job satisfaction, ability and motivation partially have a direct effect on employee performance, and ability and motivation partially have a direct effect on employee performance through job satisfaction